2019
DOI: 10.3390/app9214532
|View full text |Cite
|
Sign up to set email alerts
|

An Overall Deformation Monitoring Method of Structure Based on Tracking Deformation Contour

Abstract: Featured Application: This study aims at the lack of sufficient data supporting structural damage identification, which is a general issue in traditional single-point measurement method. A novel method has been proposed for structural deformation monitoring based on digitalized photogrammetry, with improved efficiency and reduced cost. The method can be applied in the overall deformation monitoring of engineering structures, such as bridges. Furthermore, the method can provide a solid foundation for the estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…xt field-of-vision edge pixel band point group To quantify the acquired characteristic parameters of holography geometric morphology, a fuzzy probability-based edge detection algorithm [32,33] is adopted to extract probability edges of the structure in a complex illumination condition. Moreover, the probability edge can reflect holography geometric morphology of the structure to a significant degree.…”
Section: (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…xt field-of-vision edge pixel band point group To quantify the acquired characteristic parameters of holography geometric morphology, a fuzzy probability-based edge detection algorithm [32,33] is adopted to extract probability edges of the structure in a complex illumination condition. Moreover, the probability edge can reflect holography geometric morphology of the structure to a significant degree.…”
Section: (A)mentioning
confidence: 99%
“…Notably, the movements obtained by applying this algorithm actually represent pixels. The real displacement can be obtained when the distance a pixel represents is known [33]. As shown in Equations (5), characteristic parameters of the holography geometric morphology are aligned between pixel and world coordinate systems on an image plane, so that degrees of freedom (DoF) of diverse pixels in the structure's holography geometric morphology can be acquired along axes x and y, and accordingly converted into actual displacement of the structure in the world coordinate system.…”
Section: (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-point displacement measurements for the desired accuracy have been obtained also using a single camera [3,[18][19][20]. In a laboratory environment, accurate full-field static displacements of beams have been obtained with a single camera using a photogrammetric measurement approach [21] and tracking deformation contour [22], a robotic camera system with a single camera [23], and a holographic visual sensor consisting of two cameras [24]. However, the aforementioned studies focused on short-term measurement campaigns where the camera location is fixed in a single position.…”
Section: Introductionmentioning
confidence: 99%
“…Xiao et al [10] realized the real-time measurement of straightness and roundness of spun workpieces during spinning by obtaining real-time images based on machine vision technology. Chu et al [11] proposed a digital image-based method for the overall structural deformation monitoring, utilizing the image perspective transformation and edge detection. Qiu et al [12] reported a novel method based on laser and machine vision to automatically measure tunnel deformation of multiple interest points in real time and effectively compensate for the environment vibration.…”
Section: Introductionmentioning
confidence: 99%